Endogenous fructose production and metabolism in the liver contributes to the development of metabolic syndrome - Lanaspa, Miguel A (2013)
Carbohydrates with high glycemic index are proposed to promote the development of obesity, insulin resistance and fatty liver, but the mechanism by which this occurs remains unknown. High serum glucose concentrations glucose are known to induce the polyol pathway and increase fructose generation in the liver. Here we show that this hepatic, endogenously-produced fructose causes systemic metabolic changes. We demonstrate that mice unable to metabolize fructose are protected from an increase in energy intake and body weight, visceral obesity, fatty liver, elevated insulin levels and hyperleptinemia after exposure to 10% glucose for 14 weeks. In normal mice, glucose consumption is accompanied by aldose reductase and polyol pathway activation in steatotic areas. In this regard, we show that aldose reductase deficient mice were protected against glucose-induced fatty liver. We conclude that endogenous fructose generation and metabolism in the liver represents an important mechanism whereby glucose promotes the development of metabolic syndrome.